Sierra Leone : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waivers of Nonobservance of Performance Criteria, Modification of Performance Criteria, Augmentation of Access, and Financing Assurances Review; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Sierra Leone. (IMF Staff Country Reports; Country Report ;, 2009)
This paper focuses on the Fourth Review for Sierra Leone under the Poverty Reduction and Growth Facility. Program performance in the second half of 2008 was mixed. Although economic activity slowed in the last quarter, real GDP grew at an estimated 5.5 percent for the year. A key challenge is to mobilize more domestic revenue by strengthening tax administration and broadening the tax base. The authorities are also moving to make the National Revenue Authority more efficient and raise taxpayer compliance.